Random walk tests for the Lisbon stock market - Borges, Maria Rosa (2010)
This paper reports the results of tests on the weak-form market efficiency applied to the PSI-20 index prices of the Lisbon Stock Market from January 1993 to December 2006. As an emerging stock market, it is unlikely that it is fully information-efficient, but we show that the level of weak-form efficiency has increased in recent years. We use a serial correlation test, a runs test, an augmented Dickey-Fuller test and the multiple variance ratio test proposed by Lo and MacKinlay (1988) for the hypothesis that the stock market index follows a random walk. Non-trading or infrequent trading is not an issue because the PSI-20 only includes the 20 most traded shares. The tests are performed using daily, weekly and monthly returns for the whole period and for five sub-periods which reflect different trends in the market. We find mixed evidence, but on the whole, our results show that the Portuguese stock market index has been approaching a random walk behavior since year 2000, with a decrease in the serial dependence of returns.